Preparation and properties of fluorinated silicon two‐component polyurethane hydrophobic coatings. Issue 5 (11th February 2020) - Hu, Linqing; Pu, Zejun; Tian, Yuhan; Zheng, Xiaoyi; Cheng, Jie; Zhong, Jiachun
Abstract: A polyurethane (PU) hydrophobic coating was prepared by the two‐component method, polycarbonate diol and isophorone diisocyanate becoming a two‐phase composition. The PU films with hydrophobic surface were prepared by establishing a rough structure on the surface of silica (SiO2 ) modified with silane coupling agents (γ‐(2, 3‐epoxypropoxy)propytrimethoxysilane (KH560) and (heptadecafluoro‐1, 1, 2, 2‐tetradecyl)trimethoxysilane (FAS)). First, the surface of SiO2 was covered by a layer of hydrophobic methyl and fluorocarbon (C–F) groups. Then, the SiO2 and modified SiO2 were obtained by the introduction of KH560 and FAS with the silanol reaction by ultrasonic stirring. The effect of SiO2 and modified SiO2 on the structure and hydrophobic properties of PU was investigated by a series of test instruments. The results showed that the introduction of SiO2 and modified SiO2 was beneficial for increasing the roughness of the PU coating surface; the roughness of FAS/SiO2 ‐PU could reach up to 14.790 nm, four times better than pure PU. A hydrophobic modified PU coating with water contact angle 123° was fabricated by using the hydrophobic C–F group FAS as a low surface energy material and establishing a micro rough structure on the surface of PU. Moreover, PU modified with KH560 and FAS can reduce the glass transition temperature ( T g ) of soft segments, resulting in improvement of micro‐phase separation. © 2020 Society of Chemical Industry Abstract : The synthetic route of FAS/SiO2 ‐PU hydrophobic coating (FAS, (heptadecafluoro‐1, 1, 2, 2‐tetradecyl)trimethoxysilane; PU, polyurethane).